Zircon SHRIMP U-Pb Dating and Significance From Weathered Residual Kaolin Deposits on the Northern Margin of the Qinzhou-Hangzhou Suture Zone, China - Li, Chunhai; Sun, Qifa; Sun, Zhonglin; Zhou, Xiaohua; Zhang, Wei; Chen, Rong; Gao, Tianshan (Frontiers in Earth Science, 2022)
Weathered residual Kaolin deposits on the northern margin of the Qinzhou-Hangzhou Suture Zone are characterized by more feldspar-containing minerals and fewer dark minerals. These deposits have attracted increasing attention because of their high whiteness, low harmful impurity content, low depth of weathered mineralization, and ease for mining. The ore-forming rock masses mainly include granite (granite porphyry), quartz porphyry, eurite, haplite, and other acidic veins; the ore-bearing walls are mainly of Upper Proterozoic. Previous studies suggested that dyke rocks related to Kaolin deposits in this belt belong to the Mesozoic, but there is a lack of information regarding specific mineralization ages. In this study, two dyke wall-type weathered residual Kaolin deposits were selected from the northern margin of the Qinzhou-Hangzhou Suture Zone (Dongxicun and Yinbeidong, Jiangxi Province, China) for zircon SHRIMP dating. Two zircon U-Pb-based ages were obtained: 843 ± 10 Ma from Dongxicun granite veins that intrude into the Neoproterozoic Jiuling rock masses; 152.3 ± 1.8 Ma for Yinbeidong granite porphyry veins that intrude into the Neoproterozoic Anlelin Formation. We suggest that the dykes related to the Kaolin deposits were formed in the Neoproterozoic and late Jurassic. The Neoproterozoic dyke may be related to the convergence, formation, or pyrolysis of the Rodinia Supercontinent and the late Jurassic dyke may be related to the subduction of the Paleo-Pacific Plate. These results provide a chronological basis for the investigation and evaluation of weathered residual Kaolin deposits on the Qinzhou-Hangzhou Suture Zone.